Oxygen‐Driven Metal–Insulator Transition in SrNbO3 Thin Films Probed by Infrared Spectroscopy. (11th March 2022) - Di Pietro, Paola; Bigi, Chiara; Chaluvadi, Sandeep Kumar; Knez, Daniel; Rajak, Piu; Ciancio, Regina; Fujii, Jun; Mercuri, Francesco; Lupi, Stefano; Rossi, Giorgio; Borgatti, Francesco; Perucchi, Andrea; et al.
Abstract: The occurrence of oxygen‐driven metal–insulator‐transition (MIT) in SrNbO3 (SNO) thin films epitaxially grown on (110)‐oriented DyScO3 has been reported. SNO films are fabricated by the pulsed laser deposition technique at different partial O2 pressure to vary the oxygen content and their structural, optical, and transport properties are probed. SNO unit cell has been found to shrink vertically as the oxygen content increases but keeping the epitaxial matching with the substrate. The results of Fourier‐transform infra‐red spectroscopy show that highly oxygenated SNO samples (i.e., grown at high oxygen pressure) show distinct optical conductivity behavior with respect to oxygen deficient films, hence demonstrating the insulating character of the formers with respect to those fabricated with lower pressure conditions. Tailoring the optical absorption and conductivity of strontium niobate epitaxial films across the MIT will favor novel applications of this material. Abstract : Oxygen‐driven metal–insulator‐transition in SrNbO3 has been reported. Thin films are epitaxially grown on DyScO3 substrates by pulsed laser deposition at different oxygen pressure. Fourier‐transform infra‐red spectroscopy identifies three major contributions in the optical conductivity, namely a Drude term, a far‐infrared band, and a mid‐infrared band. This work indicates SrNbO3 as an ideal candidate for multi‐layered epitaxial oxide heterostructures.